Compact laser wakefield acceleration toward high energy with micro-plasma parabola - Xuesong Geng; Tongjun Xu; Lingang Zhang; Igor Kostyukov; Alexander Pukhov; Baifei Shen; Liangliang Ji (Matter and Radiation at Extremes, 2024)
Laser wakefield acceleration (LWFA) promises compact accelerators toward the high-energy frontier. However, the approach to the 100 GeV milestone faces the obstacle of the long focal length required for optimal acceleration with high-power lasers, which reaches hundreds of meters for 10–100 PW lasers. The long focal length originates from optimal laser intensity required to avoid nonlinear effects and hence large spot size and Rayleigh length. We propose a “telescope” geometry in which a micro-plasma parabola (MPP) is coupled with a short-focal-length off-axis parabola, minimizing the focal length to the meter range for LWFA under optimized conditions driven by lasers beyond 1 PW. Full-dimensional kinetic simulations demonstrate the generation of a 9 GeV electron bunch within only 1 m optical length—only one-tenth of that required with the conventional approach with the same performance. The proposed MPP provides a basis for the construction of compact LWFAs toward single-stage 100 GeV acceleration with 100 PW class lasers.